Communication protocols and concurrency: an Occam implementation of X.25 - Kropf, Peter; Goode, Paul; Bärtschi, D.; Spichiger, Andreas; Boillat, J. E. (: IEEE, 1988)
Experience with the use of the current software and hardware offerings is presented and discussed in relation to practical implementation of the CCITT recommendation X-25. An implementation of X.25 is made using the concurrent programming language Occam and its associated hardware, the transputer. Their suitability in such an application is investigated. In particular, the simplicity of software design of communication systems based on concurrent implementation methods is reported. The implementation and its consequences are discussed, and conclusions regarding this approach are drawn.
, 1988